Analysis of Local Wisdom in Bima Community Marriage (Study of Socio-Cultural Values) - Amrin Amrin; Adi Priyono; Supriyanto Supriyanto; Nurrahmania Nurrahmania (LEGAL BRIEF, 2022)
This article aims to examine local wisdom in the marriage of the Bima community in terms of socio-cultural values. This study uses a descriptive qualitative type with an anthropological approach. The data collection method uses observation, interviews and documentation as well as literature study. While the data analysis technique is descriptive qualitative with data reduction, data presentation, and conclusion. The results of the research shows that the tradition of peta kapanca at the wedding ceremony of the Bima community has socio-cultural values that are still preserved to this day, namely friendship, mutual assistance and cooperation, and brotherhood. The research is only limited to socio-cultural values so further research is needed on the Mbojo culture as a whole so as to explore the cultural values of the Bima people which have implications for the preservation of local wisdom values in an area.